Semantic Representation of Complex Resource Requests for Service-oriented Architecture - Xing Wang; Changwang Liu (Institute of Advanced Engineering and Science, 2014)
Many open distributed systems across Internet such as those in grid computing and e-Commerce involve the requesting, allocation and maintenance of sorts of resources. The discovery of large amount of resources in different sites is an important issue for the design of these systems. The booming semantic Web technology provides a suitable infrastructure for the publishing, requesting and matchmaking of resources. This paper presents a generic representation for quantified resource requesting with Semantic Web. It allows the representation of complex resource descriptions such as containment hierarchies and disjoint constraints between them. A model-theoretic semantics for matchmaking with countable resources is given for this representation. A constraint-based technique for the matchmaking check with such representation is designed DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3350